Pelas ruas e nas páginas das revistas: estratégias de construção da representação do morador de rua no discurso jornalístico de Ocas e VEJA São Paulo São Paulo - Almeida Junior, Guy Pinto de (2014)
The theme of this dissertation is the representation of the homeless in São Paulo on journalistic discourse in magazines Ocas and VEJA São Paulo. Our main goal is to analyze the strategies of journalistic discourse in relation to the social representation of the homeless in these publications. The secondary objectives are: conceptualizing city , poverty and concept of difference in order to relate the three concepts to the phenomenon of consumption, identify the social representations of the homeless on journalistic discourse in both magazines; identify strategies for production of meaning of journalistic discourses on the subject street dwellers in each publishing, and compare the identified strategies of production of meaning to think about some logic in production of journalistic discourse about the concept of difference. As for theoretical reasons, the analysis of discourse is our main theoretical foundation, to be understood within the theories of journalism, city and the concept of difference. We also undertook an empirical research of documental nature, which resulted in a set of 203 journalistic articles published in the magazines from 2005 to 2012 on the theme of homeless of São Paulo s city, from which we developed two corpora: the Ocas (16 texts) and VEJA São Paulo (15 texts). On the analysis, we highlight the following results: in Ocas , the street dweller is represented as a holder of citizen rights, while in VEJA São Paulo, he is represented as a strange individual in relation to the regulation of the city. Given these results, we can say that the journalistic discourse of both magazines houses and reproduces stereotypes and social disqualification of the homeless.